Using standardised vignettes to assess practicum competencies in psychology and other disciplines : Final Report. - Consalvez, Craig; Terry, Josephine; Deane, Frank P. (Office for Learning and Teaching, 2016)
This project adopted a novel approach to address unsatisfactory reliability and validity of field supervisor ratings, a problem that has plagued assessment of practicum competencies for decades. The hallmark of the new approach is the use of a set of standardised vignettes in lieu of domain items on the conventional Likert rating scale. The new instrument, the Vignette Assessment Tool (VAT) will comprise 41 vignettes that anchor different developmental stages for each of ten clinical psychology competency domains. The current project built upon a recently completed, ALTC-funded, pilot project that demonstrated superior results for the vignette method. The project standardised and calibrated the catalogue of vignettes, developed an online platform to administer it, conducted a multisite (including two international sites) trial of the VAT, and established a normative data set that will inform its use and interpretation. The project also pilot crossed disciplinary and international applications of the VAT.